Ozonized water, background, general use in medicine and preclinic support (Ozone Therapy Global Journal, 2019)
The use of ozonized water (O3W) is now gaining in importance in medicine. Ozone is dissolved in its molecular form (O3). In this review, the bibliographical data concerning the general use of O3W in medicine and preclinical support is analyzed. The search included a review of scientific articles and experimental results papers in the MEDLINE and Zotero ISCO3 Ozone Database, between the years 1980-2018. Descriptors used was: ozonized water, ozonized solutions. The primary (original articles) sources of information were located. Main indications of O3W involve the control of local infections: ulcus cruris, decubitus ulcers, mycosis, mycotic infections, herpes simplex and herpes zoster, burns, also superinfected burns, intraoperative rinsing, eye injuries and infections, surgical scars (healing: primary or secondary), and edemas of traumatic or bacterial origin. In addition, O3W is also applied on account of its pain-relieving and anti-inflammatory effects, as well as its tissue-activating properties in acute and chronic injuries with and without infection. O3W is also being used intraoperatively for rinsing (disinfection), as in hand disinfection in surgery, in dental medicine (including the disinfection of tools and water), rinsed in conditions such as thrush and periodontal disease, in primary root canal disinfection and particularly in oral surgery. O3W also can play an important role as a potential disinfectant in controlling the problem of contamination of dental unit waterlines. O3W may also be swallowed in cases of gastritis or gastric carcinoma, or irrigated in chronic intestinal or bladder inflammation. In balneotherapy, O3W bubbled in warm baths, provides stimulation of local circulation and disinfectant action to varicosities, peripheral circulatory disorders and dermatological conditions (eczema, ulcers). Preclinical evidence supports the use of O3W in medicine and shown the importance of it use in daily medical practice...